Morphological Processes in Palembang Malay Language: Affixation, Reduplication, and Composition - Nasiatun Yasiroh; Meenakshi Vythianathan; Nosheen Jaffar (Journal of Language, Literature, and Educational Research, 2024)
Purpose of the study: This study aims to describe the forms, meanings, and functions of morphological processes in Palembang Malay language, specifically affixation, reduplication, and composition. The research also seeks to identify changes and new findings in morphological structures compared to previous studies on Palembang Malay morphology. Methodology: This study employed a descriptive qualitative approach using distributional methods. Data were collected through literature study of Palembang Malay folktales and pantun, supported by closed interviews, observation, note-taking, recording techniques, and questionnaires. The informants consisted of six native speakers from Sungai Lilin and Bayung Lencir, Musi Banyuasin Regency. Data validity used triangulation techniques. Main Findings: The findings show that Palembang Malay morphological processes consist of affixation, reduplication, and composition. Affixation includes prefixes, infixes, suffixes, and simulfixes. Reduplication consists of full reduplication, partial reduplication, affixal reduplication, and phoneme-changing reduplication. Composition includes word combinations and stem combinations. New findings were identified in simulfix forms {di-nyo} and {se-nyo}, which were absent in previous studies Novelty/Originality of this study: The novelty of this study lies in the discovery of new simulfix forms {di-nyo} and {se-nyo} in Palembang Malay, which were not found in previous morphological studies. This research also updates earlier findings after a 34-year gap and strengthens the documentation of regional language preservation through a detailed analysis of contemporary morphological structures.